1986
DOI: 10.1126/science.3787262
|View full text |Cite
|
Sign up to set email alerts
|

Selective Chemical Catalysis by an Antibody

Abstract: The immunoglobulin MOPC167, which binds the transition state analog p-nitrophenylphosphorylcholine with high affinity, catalyzed the hydrolysis of the corresponding carbonate 1. MOPC167 catalysis displayed saturation kinetics with catalytic constant (kcat) = 0.4 min-1 and Michaelis constant (Km) = 208 microM, showed substrate specificity, and was inhibited by p-nitrophenylphosphorylcholine. The rate of the reaction was first order in hydroxide ion concentration between pH 6.0 and 8.0. The lower limit for the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
220
0
9

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 622 publications
(233 citation statements)
references
References 27 publications
4
220
0
9
Order By: Relevance
“…For most part of antibodies, this observation is correct. At the same time during the last 30 years, it was shown that Abs against chemically stable analogues modeling the transition states of chemical reaction can catalyze many different reactions [1][2][3][4][5][6][7][8]. Such artificial catalytic antibodies were called abzymes (derived from antibody enzymes).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For most part of antibodies, this observation is correct. At the same time during the last 30 years, it was shown that Abs against chemically stable analogues modeling the transition states of chemical reaction can catalyze many different reactions [1][2][3][4][5][6][7][8]. Such artificial catalytic antibodies were called abzymes (derived from antibody enzymes).…”
Section: Introductionmentioning
confidence: 99%
“…Such artificial catalytic antibodies were called abzymes (derived from antibody enzymes). Abzymes (Abzs) can catalyze more than 200 different chemical reactions and are new biological catalysts attracting great interest during recent years and are well described (for review see [1][2][3][4][5][6][7][8] and refs therein).…”
Section: Introductionmentioning
confidence: 99%
“…However, although it is possible in principle to modify the active site of any native enzyme to generate nonnatural activity, this approach has met with only limited success because of the difficulties involved in predicting the effect of sequence modifications on structure and function. Catalytic antibodies based on the properties of the immune system in generating binding sites that are complementary to transition-state analogues have been shown to be efficient catalysts for numerous chemical reactions (15)(16). Their catalytic efficiencies, based mainly on transition-state stabilization, have been shown to be comparable with those at the lower end of naturally occurring enzymes, and they may improve further as our understanding of how to design transition-state analogues develops (17).…”
mentioning
confidence: 99%
“…Phosphonate derivatives were the first and most successful haptens to elicit tailor-made esterolytic catAbs. They show good approximation of the transition state of substrates for ester hydrolysis because of their tetrahedral geometry and anionic character (3,4). Since then, a variety of catAbs has been generated based on haptenic TSAs (5).…”
mentioning
confidence: 99%